The impact of Theraplay® therapy on parent-child interaction and child psychiatric symptoms: a pilot study. Issue 3 (2nd July 2020) - Salo, Saara; Flykt, Marjo; Mäkelä, Jukka; Lassenius-Panula, Lotta; Korja, Riikka; Lindaman, Sandra; Punamäki, Raija-Leena
ABSTRACT: Theraplay® is a short-term parent–child interaction therapy combining structured, attachment-based, joyful and adult-led playful sessions with reflective guidance work with the parents. This pilot study evaluates the impact of Theraplay® therapy in improving the quality of parent–child interaction and decreasing the internalizing and externalizing symptoms of children diagnosed with emotional and/or behavioral disorders. Participants were eighteen 4–8 year-old children ( M = 4.42, SD = 1.54) from two outpatient child psychiatric clinics whose mothers, and in 13 of those cases fathers also participated in the Theraplay® therapy together with the child. Pre- and post-treatment measures included videotaped observations of parent–child interaction quality, and child psychiatric symptoms (CBCL). The results showed improvements in parent–child interaction quality as well as decreases in children's internalizing and externalizing symptoms. The results of this pilot study indicate that Theraplay® therapy may be an effective treatment among children diagnosed with emotional and/or behavioral psychiatric disorders.